A coverless information hiding algorithm based on gradient matrix. (8th May 2020) - Wu, Jianbin; Luo, Chuwei; Kang, Ziyang; Ge, Shuangkui; Xin, Yemin
A coverless information hiding algorithm based on gradient matrix is introduced in this paper. Firstly, we grid the sharpened gradient matrix of an image. Then we encode the spectral radius of the gridded matrix to construct the mapping relationship between the matrix eigenvalues and random numbers. In order to improve the efficiency and security of transmission, we process the information segment by BCH (31, 21) encoder, in which redundancy check bits are added to detect and recover the errors caused by the interference in communication, thus breaking the limit that the image library has to be shared between the sender and receiver. In the meantime, splicing strategy is adopted to reduce the difficulty of building image library with the length of information sequence increasing. As the experimental results show, this proposed algorithm has a strong robustness towards glitch attack, JPEG compression attack, etc. and has a great application value in high-level secret key communication.